Fear of crime in the United States: causes, consequences and contradictions - Lane, Jodi (Carolina Academic Press, 2014)
The current state of fear of crime in America : a broad overview -- Reviewing the fear of crime literature : what has been learned from 45 years of research? -- Measuring fear of crime over the years : sundry methods muddle the validity -- Gender : the most consistent predictor of fear of crime -- How and why age, race/ethnicity, and socioeconomic status contribute to fear of crime -- The influence of contextual predictors on fear of crime : personal experience, indirect victimization, and community -- Consequences of fear of crime : physical, psychological, behavioral, and social effects -- Tying the findings together : suggestions for policy and future research on fear of crime